Influence of Ionic Strength, pH, and Cation Valence on Aggregation Kinetics of Titanium Dioxide Nanoparticles - French, Rebecca A; Jacobson, Astrid R; Kim, Bojeong; Isley, Sara L; Penn, R. Lee; Baveye, Philippe C (Environmental science & technology, 2009)
The extensive use of titanium dioxide nanoparticles (nano-TiO2) in many consumer products has raised concerns about possible risks to the environment. The magnitude of the threat may depend on whether nano-TiO2 remains dispersed in the environment, or forms much larger-sized aggregates or clusters. Currently, limited information is available on the issue. In this context, the purpose of the present article is to report initial measurements of the morphology and rate of formation of nano-TiO2 aggregates in aqueous suspensions as a function of ionic strength and of the nature of the electrolyte in a moderately acid to circumneutral pH range typical of soil and surface water conditions. Dynamic light scattering results show that 4−5 nm titanium dioxide particles readily form stable aggregates with an average diameter of 50−60 nm at pH ∼4.5 in a NaCl suspension adjusted to an ionic strength of 0.0045 M. Holding the pH constant, but increasing the ionic strength to 0.0165 M, leads to the formation of micron-sized aggregates within 15 min. At all other pH values tested (5.8−8.2), micron-sized aggregates form in less than 5 min (minimum detection time), even at low ionic strength (0.0084−0.0099 M with NaCl). In contrast, micron-sized aggregates form within 5 min in an aqueous suspension of CaCl2 at an ionic strength of 0.0128 M and pH of 4.8, which is significantly faster than observed for NaCl suspensions with similar ionic strength and pH. This result indicates that divalent cations may enhance aggregation of nano-TiO2 in soils and surface waters. Optical micrographs show branching aggregates of sizes ranging from the 1 μm optical limit of the microscope to tens of micrometers in diameter.